2006
DOI: 10.2337/dc06-0952
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Adiponectin Levels With Incident Impaired Glucose Metabolism and Type 2 Diabetes in Older Men and Women

Abstract: OBJECTIVE -Adiponectin is an adipose tissue-derived protein. Low levels are associated with obesity, insulin resistance, and type 2 diabetes. Our objective was to investigate the prospective association between adiponectin levels and the 6.4-year risk of type 2 diabetes and of impaired glucose metabolism (IGM). RESEARCH DESIGN AND METHODS -The Hoorn Study is a cohort study amongCaucasians, aged 50 -75 years. BMI, waist-to-hip ratio (WHR), fasting glucose, 2-h glucose, triglycerides, HDL cholesterol, LDL choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

22
125
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(156 citation statements)
references
References 27 publications
22
125
1
8
Order By: Relevance
“…34,53,54 In fact, female mice consistently showed much higher levels of adiponectin in plasma compared with males, including the biologically active HMW form, 47 and this feature was independent of the type of diet, expression of inflammatory markers in adipose tissue and duration of HF feeding. These results are in accordance with other animal 36,55,56 as well as human 57,58 studies showing higher adiponectin levels in females and suggesting involvement of adipose tissue expandability in the beneficial metabolic effects of adiponectin. 36 .…”
Section: Discussionsupporting
confidence: 92%
“…34,53,54 In fact, female mice consistently showed much higher levels of adiponectin in plasma compared with males, including the biologically active HMW form, 47 and this feature was independent of the type of diet, expression of inflammatory markers in adipose tissue and duration of HF feeding. These results are in accordance with other animal 36,55,56 as well as human 57,58 studies showing higher adiponectin levels in females and suggesting involvement of adipose tissue expandability in the beneficial metabolic effects of adiponectin. 36 .…”
Section: Discussionsupporting
confidence: 92%
“…It has also been documented that adiponectin concentrations were higher in women than in men (34). A recent study suggests that the associations between circulating adiponectin levels and diabetes risk may be different in men and women (35). In addition, body fat may affect the expression of adiponectin and ADIPORs (29,36).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the fullycontrolled nature of the nutritional phase permitted to document sex differences in adipocytokine responses to the MedDiet with a maximum of control over confounding variables. In addition, since previous studies have suggested that associations between these adipocytokines and cardiovascular risk factors may be sex-specific 5,6,12,13 , the inclusion of both men and premenopausal women allowed us to document for the first time sex-related differences in these associations in response to the MedDiet. On the other hand, one limitation of the present study is the absence of a control diet, which limits the conclusions on true treatment effects.…”
Section: !%" "mentioning
confidence: 99%
“…Moreover, some previous studies have found sex-related differences in the link between these adipose tissuederived hormones and the development of type 2 diabetes. In fact, the association between leptin concentrations and type 2 diabetes has been shown to be stronger in men than in women 5,6 while adiponectin concentrations would be more closely associated with type 2 diabetes in women than in men 12 . Sex-related differences have also been found in the relationship between blood concentrations of these adipocytokines and markers of cardiovascular risk 11,13 .…”
Section: Introductionmentioning
confidence: 99%